The Ends of European Colonial Empires
XII, 288 p.
Keywords: This volume provides a multidimensional assessment of the diverse ends of the European colonial empires, addressing different geographies, taking into account diverse chronologies of decolonization, and evaluating the specificities of each imperial configuration under appreciation (Portuguese, Belgian, French, British, Dutch).